Multimodal Imaging in Neurofibromatosis Type 1-associated Nerve Sheath Tumors - Salamon, J.; Mautner, V. F.; Adam, G.; Derlin, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Neurofibromatosis type 1 (NF1) is a neurogenetic disorder. Individuals with NF1 may develop a variety of benign and malignant tumors of which peripheral nerve sheath tumors represent the most frequent entity. Plexiform neurofibromas may demonstrate a locally destructive growth pattern, may cause severe symptoms and may undergo malignant transformation into malignant peripheral nerve sheath tumors (MPNSTs). Whole-body magnetic resonance imaging (MRI) represents the reference standard for detection of soft tissue tumors in NF1. It allows for identification of individuals with plexiform neurofibromas, for assessment of local tumor extent, and for evaluation of whole-body tumor burden on T2-weighted imaging. Multiparametric MRI may provide a comprehensive characterization of different tissue properties of peripheral nerve sheath tumors, and may identify parameters associated with malignant transformation. Due to the absence of any radiation exposure, whole-body MRI may be used for serial follow-up of individuals with plexiform neurofibromas. 18F-fluorodeoxyglucose positron-emission-tomography (FDG PET/CT) allows a highly sensitive and specific detection of MPNST, and should be used in case of potential malignant transformation of a peripheral nerve sheath tumor. PET/CT provides a sensitive whole-body tumor staging. The use of contrast-enhanced CT for diagnosis of peripheral nerve sheath tumors is limited to special indications. To obtain the most precise readings, optimized examination protocols and dedicated radiologists and nuclear medicine physicians familiar with the complex and variable morphologies of peripheral nerve sheath tumors are required.Key points:• Individuals with NF1 may develop benign and malignant nerve sheath tumors.• Whole-body MRI is the reference standard to identify nerve sheath tumors in NF1.• MRI provides a comprehensive characterization of the growth pattern, growth dynamics and extent of nerve sheath tumors.• 18F-FDG PET/CT provides a sensitivity of 100 % and a specificity of 77 – 95 % for detection of malignant transformation.Citation Format:• Salamon J, Mautner VF, Adam G et al. Multimodal Imaging in Neurofibromatosis Type 1-associated Nerve Sheath Tumors. Fortschr Röntgenstr 2015; 187: 1084 – 1092
Keywords: NF1; neurofibromatosis; MPNST; MRI; PET